2021
DOI: 10.1016/j.ejphar.2020.173650
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-binding domain extends half-life of glucagon-like peptide-1

Abstract: Glucagon-like peptide-1 (GLP-1) is considered to be a promising peptide for the treatment of type 2 diabetes mellitus (T2DM). However, the extremely short half-life of GLP-1 limits its clinical application. Albumin-binding domain (ABD) with high affinity for human serum albumin (HSA) has been used widely for half-life extension of therapeutic peptides and proteins. In the present study, novel GLP-1 receptor agonists were designed by genetic fusion of GLP-1 to three kinds of ABDs with different affinities for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…As an example of the power of this approach, an albumin binding domain with high affinity for human serum albumin was used to circumvent the short half-life of Glucagon-like peptide-1 (GLP-1), a promising peptide for the treatment of type 2 diabetes mellitus. Three different ABD-fusion GLP-1 proteins bound HSA with high affinity, extended its half-life, and improved the glucose-lowering effect of GLP-1 ( 318 ). Studies like this have important implications for altering in vivo pharmacokinetics of peptides and proteins to improve pharmacodynamic and pharmacokinetic properties.…”
Section: Albumin As a Therapeutic Half-life-extending Agentmentioning
confidence: 99%
“…As an example of the power of this approach, an albumin binding domain with high affinity for human serum albumin was used to circumvent the short half-life of Glucagon-like peptide-1 (GLP-1), a promising peptide for the treatment of type 2 diabetes mellitus. Three different ABD-fusion GLP-1 proteins bound HSA with high affinity, extended its half-life, and improved the glucose-lowering effect of GLP-1 ( 318 ). Studies like this have important implications for altering in vivo pharmacokinetics of peptides and proteins to improve pharmacodynamic and pharmacokinetic properties.…”
Section: Albumin As a Therapeutic Half-life-extending Agentmentioning
confidence: 99%
“…Recently, HSA fusion technology has also been utilized for extending the half-life of therapeutic proteins because of the special kinetic properties of HSA 65 , 66 . The mechanism of HSA fusion in prolonging half-life is the same as Fc fusion 67 , 68 .…”
Section: Existing Strategies To Manipulate the Drug In Vivo Clearancementioning
confidence: 99%
“…For instance, when researchers discovered the benefits of GLP-1 in diabetes and developed a therapeutic analog, they found that the native human GLP-1 (7-37) half-life was too short to have the desired therapeutic effect (Deacon et al, 1995). Lipidation of the peptide provided an extended half-life and thus brought liraglutide to clinical utility (Knudsen et al, 2000;Tan et al, 2021;Victoza, 2022). Modification of the naturally occurring alanine in position 8 of hGLP-1 (7-37) to the UAA aminoisobutyric acid (Aib) prevented degradation by dipeptidyl peptidase IV (DPP-IV) and further increased the half-life (Deacon et al, 1995), bringing semaglutide to the market (Ozempic, 2022;Rybelsus, 2022).…”
Section: Immunogenic Risk Assessment For Unnatural Amino Acid-contain...mentioning
confidence: 99%
“…First, the lysine in position 26 has been modified with a C18 diacid connected to the lysine side chain via a mini PEG spacer and γ-glutamic acid (OEG-OEG-γGlu-C18 diacid). The fatty acid chain reversibly binds human serum albumin in vivo while the mini PEG spacer provides flexibility to allow for improved binding to the receptor (Tan et al, 2021). Additionally, a modification from lysine to arginine in position 34 was introduced to ensure direct fatty acid conjugation to the lysine in position 26 (Knudsen et al, 2000).…”
Section: Example 2 Semaglutide Active Pharmaceutical Ingredientmentioning
confidence: 99%